Silicon enrichment of an austenitic stainless steel – Impact on electrochemical behavior in concentrated nitric acid with oxidizing ions. (1st November 2019) - Laurent, Barbara; Gruet, Nathalie; Gwinner, Benoit; Miserque, Frédéric; Soares-Teixeira, Vinicius; Ogle, Kevin
Abstract: The effect of a 3.5 wt % addition of Si on the corrosion resistance of an 18Cr–15Ni stainless steel (SS) in 100 °C nitric acid, HNO3 was investigated using transmission electron spectroscopy, X-ray photoelectrons spectroscopy, linear scan voltammetry and electrochemical impedance spectroscopy. The X1CrNiSi18-15-4 SS was compared to the X2CrNiN18-10 SS in various types of conditions: pure concentrated HNO3 with or without oxidizing species (V(V) and Cr(VI)). In pure HNO3, both SS are passive and the X1CrNiSi18-15-4 SS dissolves spontaneously faster than the X2CrNiN18-10 SS. The addition of oxidizing species V(V) or Cr(VI) in the electrolyte leads to the opposite result: the X1CrNiSi18-15-4 SS remains in the passive state, whereas the 18Cr–10Ni SS is polarized in the transpassive state. As a consequence, the X1CrNiSi18-15-4 SS corrodes slower than the X2CrNiN18-10 SS. All these observations demonstrate that the presence of Si in the oxide film slightly deteriorates the passivity of the SS but also moderates the reduction processes. It keeps the corrosion potential of the X1CrNiSi18-15-4 SS low enough for the alloy to remain passive even if oxidizing species are present in the electrolyte. A specific impact of the addition of Cr(VI) is also shown, as Cr(VI) seems to play a role on both cathodic and anodic processes, whereas V(V) mainly impacts the cathodic kinetics.